Human shellfish poisoning: Implementation of a national surveillance program in France - Sinno-Tellier, Sandra; Abadie, Eric; Guillotin, Sophie; Bossée, Anne; Nicolas, Marina; Delcourt, Nicolas (Frontiers in Marine Science, 2023)
Toxic algae and their toxins represent an emerging public health issue, particularly due to global warming. The toxicological mechanisms of neurotoxic phycotoxins and their human health effects have been widely described (paralytic, neurological, amnesic, and ciguateric toxins). Food poisoning by bivalve shellfish (mussels, oysters…) can cause serious or even fatal neurological disorders, as bivalves accumulate toxins by feeding on harmful algae. However, retrospective study of human shellfish poisoning highlighted the difficulties in identifying cases related to neurotoxic phycotoxins by gathering clinical and biological diagnostic confirmations on the one hand, as well as environmental contaminations on the other. To improve the collection of shellfish poisoning data, the French Agency for Food, Environmental and Occupational Health and Safety (ANSES), French Poison Control Centers (PCCs), the French Research Institute for Exploitation of the Sea (Ifremer) and the French Defense Procurement Agency (DGA) have developed a prospective surveillance of neurotoxins from algal origin that combines monitoring of poisoning cases (clinical monitoring), of harmful algae and their toxins in shellfish production areas (environmental monitoring), as well as of toxins levels in seafood leftovers and in biological samples from poisoned subjects. This original clinical and environmental monitoring will allow us to have a more complete view of phycotoxin human exposures that are underreported, and to implement measures to protect consumers.